Manual Acupuncture at PC6 Ameliorates Acute Restraint Stress-Induced Anxiety in Rats by Normalizing Amygdaloid Noradrenergic Response - ZhengLin Zhao (Evidence-Based Complementary and Alternative Medicine, 2017)
Acupuncture improves ethanol withdrawal-induced anxiety in rats in an acupoint-dependent manner. Thus, the present study investigated the effects of acupuncture on acute restraint stress- (ARS-) induced anxiety. Male rats were exposed to ARS for 3 h followed by acupuncture at either PC6 (Neiguan), HT7 (Shenmen), or a nonacupoint (tail) once a day for three consecutive days. Five minutes after the third acupuncture treatment, anxiety-like behavior was evaluated in an elevated plus maze (EPM). Additionally, plasma corticosterone (CORT) levels were measured by radioimmunoassay and the concentrations of norepinephrine (NE) and 3-methoxy-4-hydroxy-phenylglycol (MHPG) in the central nucleus of the amygdala (CeA) were determined using high-performance liquid chromatography. Acupuncture at PC6, but not HT7 or a nonacupoint, attenuated anxiety-like behavior, but this attenuation was abolished by a postacupunctural intra-CeA infusion of NE. Acupuncture at PC6 also reduced the oversecretion of plasma CORT and inhibited increases in amygdaloid NE and MHPG induced by ARS. Further, Western blot analyses and real-time polymerase chain reaction assays revealed that acupuncture at PC6 prevented ARS-induced enhancements in the protein and mRNA expressions of tyrosine hydroxylase in the CeA. These results suggest that acupuncture performed specifically at acupoint PC6 reduces ARS-induced anxiety-like behavior by dampening amygdaloid noradrenergic responses.